2005
DOI: 10.1038/sj.onc.1209243
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 does not suppress tumorigenicity in the human gastric cancer cell line MKN45

Abstract: CDX2 is a Drosophila caudal-related homeobox transcription factor that is expressed specifically in the intestine. In mice, ectopic expression of CDX2 in the gastric mucosa gives rise to intestinal metaplasia and in one model, gastric carcinoma. In humans, increased CDX2 expression is associated with gastric intestinal metaplasia and tubular adenocarcinomas. These patterns of expression have shown that CDX2 is important for the initiation of intestinal metaplasia in the gastric mucosa, but the role of CDX2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…Cdx2 may have a similar function in gastric cancer. However, Dang et al reported that Cdx2 does not suppress tumorigenicity in the human gastric cancer cell line MKN45 (26). Further investigations are necessary to fully elucidate the function and regulatory mechanism of Cdx2 expression, regardless of histological type or differentiation grade.…”
Section: Discussionmentioning
confidence: 99%
“…Cdx2 may have a similar function in gastric cancer. However, Dang et al reported that Cdx2 does not suppress tumorigenicity in the human gastric cancer cell line MKN45 (26). Further investigations are necessary to fully elucidate the function and regulatory mechanism of Cdx2 expression, regardless of histological type or differentiation grade.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that Cdx2 may act as a tumor suppressor gene in the GC BGC823 cell line. However, it has been reported that Cdx2 does not suppress tumorigenicity in the human GC MKN45 cell line (25). Further investigations will be required to clarify the mechanisms that are involved in the regulation of Cdx2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…CDX2 appears to contribute to oncogenic potential in a mouse model of leukemia and with this report, two colon cancer cell lines. However, we have observed that CDX2 does not suppress tumorigenicity in the human gastric cancer cell line MKN45 (Dang et al, 2006). Certainly, further investigations are warranted and ongoing.…”
Section: Cdx2 Has Tumorigenic Potential In Colon Cancer Cells Lh Dangmentioning
confidence: 95%